Digital Transformation in MSMEs: A PRISMA 2020 Based Systematic Literature Review of Adoption Drivers, Barriers, and Business Performance Implications in Emerging Economies - Loso Judijanto; IGP Ratih Andaningsih; Nashirotun Nisa Nurharjanti; Ahmad Eko Saputro (Westscience Press, 2026)
Digital transformation has become a crucial strategy for improving the competitiveness and sustainability of Micro, Small, and Medium Enterprises (MSMEs), particularly in developing countries where small businesses play a dominant role in economic growth and employment generation. This study aims to systematically review the existing literature on digital transformation in MSMEs, with a focus on identifying the key drivers, barriers, and business performance implications associated with digital adoption. The study employs a Systematic Literature Review (SLR) approach based on the PRISMA 2020 framework to ensure a transparent and rigorous process in selecting and analyzing relevant studies. A total of 18 academic articles obtained from the Google Scholar database were analyzed to synthesize current research trends and findings related to digital transformation in MSMEs in developing countries. The results reveal that the primary drivers of digital transformation include technological advancement, increasing market competition, government support programs, and organizational readiness. At the same time, several barriers hinder the digitalization process among MSMEs, including limited financial resources, lack of digital skills, inadequate technological infrastructure, and resistance to organizational change. Despite these challenges, the reviewed studies consistently indicate that digital transformation contributes positively to MSME performance by improving operational efficiency, expanding market access, enhancing customer engagement, and strengthening business resilience in uncertain economic environments. The findings of this study highlight the importance of supportive policies, digital literacy development, and improved technological infrastructure to accelerate digital adoption among MSMEs in developing countries. This study contributes to the existing literature by providing a comprehensive synthesis of research findings and offering insights for policymakers, researchers, and practitioners seeking to promote sustainable digital transformation in small business sectors.